Comparison of Insect Diversity in Long Bean (Vigna sinensis L.) and Corn (Zea mays) Plantations in Banjarsari Village, Serang City, Banten - Riski Andrian Jasmi; Uum Meiliana; Habil Nursyamsul; Mirtha Asalisa; Rifan Oktadiansyah; Ammar Miftah Farid; Siti Yulyatunnikmah (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
This study aims to compare the diversity of insect species and their ecological roles in two types of crops, namely long beans (Vigna sinensis L.) and corn (Zea mays), cultivated in Banjarsari Village, Serang City, Banten. The study was conducted over two days in March 2025, utilizing observation and sampling methods with a single-sweep technique in both the morning and afternoon sessions. The results showed that the long bean plantation had higher insect diversity compared to the corn plantation. In total, 14 insect species were identified, belonging to 11 families and five orders, with ecological functions classified as herbivores, predators, and pollinators. The species Valanga nigricornis was the most dominant herbivore, especially on long bean plants. Meanwhile, species from the Formicidae and Libellulidae families acted as natural predators, and the species Apis cerana and Ropalidia marginata functioned as pollinators. Environmental factors, including vegetation type, soil moisture, and food availability, influenced the presence of various insect types. The results of this study underscore the significance of insect diversity as an indicator of agricultural ecosystem stability, as well as a crucial component in the management of sustainable agroecosystems.